Physiological and Gene Expression Changes of Clematis crassifolia and Clematis cadmia in Response to Heat Stress - Hu, Qingdi; Qian, Renjuan; Zhang, Yanjun; Zhang, Xule; Ma, Xiaohua; Zheng, Jian (Frontiers in Plant Science, 2021)
Clematis is an superior perennial ornamental vine known for varied colors and shapes of its flowers. Clematis crassifolia is sensitive to high temperature, while Clematis cadmia has a certain temperature adaptability. Here we analyzed the potential regulatory mechanisms of C. crassifolia and C. cadmia in response to heat stress by studying the photosynthesis, antioxidant parameters, amino acids and gene expression patterns under three temperature treatments. Heat stress caused the fading of leaves, decreased net photosynthetic rate, stomatal conductance, superoxide dismutase and catalase activity, increased 13 kinds of amino acids content, and up-regulated the expression of 7 genes, including C194329_G3, C194434_G1 and C188817_g1, etc, in C. crassifolia plants. Under the treatments of heat stress, the leaf tips of C. cadmia were wilted, the net photosynthetic rate and soluble protein content decreased, with the increase of 12 amino acids content and the expression of c194329_g3, c194434_g1 and c195983_g1. Our results showed that C. crassifolia and C. cadmia had different physiological and molecular response mechanisms to heat stress during the ecological adaptation.